Gray-zone Lymphoma Between cHL and Large B-Cell Lymphoma: A Histopathologic Series From the LYSA. (March 2019) - Sarkozy, Clémentine; Copie-Bergman, Christiane; Damotte, Diane; Ben-Neriah, Susana; Burroni, Barbara; Cornillon, Jérome; Lemal, Richard; Golfier, Camille; Fabiani, Bettina; Chassagne-Clément, Catherine; Parrens, Marie; Herbaux, Charles; et al.
Abstract : Gray-zone lymphoma (GZL) with features intermediate between classic Hodgkin lymphoma (cHL) and large B-cell lymphoma (LBCL) was introduced as a provisional entity into the World Health Organization classification in 2008. However, as diagnostic criteria are imprecise, reliable identification of GZL cases remains challenging. Here, we describe the histopathologic features of 139 GZL cases from a retrospective Lymphoma Study Association (LYSA) study with the goal to improve classification accuracy. Inclusion criteria were based on literature review and an expert consensus opinion of the LYSA hematopathologist panel. We observed 86 cases with a morphology more closely related to cHL, but with an LBCL immunophenotype based on strong and homogenous B-cell marker expression (CD20 and/or CD79a, OCT2, BOB1, PAX5) on all tumor cells (cHL-like GZL). Fifty-three cases were morphologically more closely related to LBCL but harbored a cHL immunophenotype (LBCL-like GZL). Importantly, we observed a continuous morphologic and immunophenotypic spectrum within these 2 GZL categories. The majority of cases presented genetic immune escape features with CD274/PDCD1LG2 and/or CIITA structural variants by fluorescence in situ hybridization. Patients without mediastinal involvement at diagnosis (17%) were older than those with mediastinal tumors (median: 56 vs. 39 y). Cases associated with Epstein-Barr virus (24%) presented with similar patient characteristics and outcome as Epstein-Barr virus negative cases. In summary, we provide refined diagnostic criteria that contribute to a more precise pathologic and clinical characterization of GZL within a broad spectrum from cHL-like to LBCL-like disease. Abstract : Supplemental Digital Content is available in the text.